Hair-Pulling Does Not Necessarily Serve an Emotion Regulation Function in Adults With Trichotillomania - Lochner, Christine; Demetriou, Salome; Kidd, Martin; Coetzee, Bronwynè; Stein, Dan J. (Frontiers in Psychology, 2021)
Background: Trichotillomania (TTM) has been associated with childhood trauma and perceived stress. While it has been hypothesized that hair-pulling regulate negative emotions, the relationship between childhood trauma, perceived stress, emotion regulation, and hair-pulling has not been well studied. Methods: Fifty-six adults with TTM and 31 healthy controls completed the Childhood Trauma Questionnaire (CTQ), Perceived Stress Scale (PSS), and Difficulties in Emotion Regulation Scale (DERS). Hair-pulling severity was measured with the Massachusetts General Hospital-Hair Pulling Scale. CTQ, PSS, and DERS total scores were compared across groups using ANCOVA and the correlation between hair-pulling severity and emotion dysregulation was determined. Regression analyses were used to estimate the association of CTQ and PSS totals with DERS , and to determine whether associations between predictors and dependent variable (DERS) differed across groups. Results: TTM patients reported higher rates of childhood trauma (p <= 0.01), perceived stress (p = 0.03), and emotion dysregulation (p <= 0.01). There was no association between emotion dysregulation and pulling severity (r = -0.02, p = 0.89). Perceived stress was associated with emotion dysregulation in both groups (p < 0.01), and no association between childhood trauma and emotion dysregulation in either group. Perceived stress was the only significant predictor of emotion dysregulation in both groups (F=28.29, p < 0.01). Conclusion: The association between perceived stress and emotion dysregulation is not specific to TTM, and there is no association between emotion dysregulation and hair-pulling severity, suggesting that key factors other than emotion dysregulation contribute to hair-pulling. Alternative explanatory models are needed.